Current Situation of Plastic and its Recycling as Material for Rural Construction (London Journal of Research In Science: Natural and Formal, 2024)
The circular and climate-neutral plastics economy uses and manages plastics in a sustainable way. These days, there is an excessive accumulation of plastic waste and its recycling has become paramount. Polyethylene terephthalate (PET) and polypropylene (PP) are among the most consumed and wasteful plastics. One solution to repel these wastes is to recycle them into construction materials. The objective of this work was to develop a hybrid material between recycled PET and PP plastics and aggregate material to be used as paving stones in rural construction floors. The best combinations were obtained for pavers, presenting compression values between 20 and 25 Mpa and flexural- traction values of ± 10 Mpa, which are comparable to concrete or concrete blocks and pavers, but with a much lower weight. The percentage of water and humidity absorption obtained was ≤ 1%, which is within the permissible limits under the ECUATORIAN STANDARD INEN 3040 for concrete pavers and the EUROPEAN STANDARD UNE EN 1338 for cement and concrete prefabricated products. Obtaining light, resistant and low cost materials that can serve as an option to conventional construction materials.
Keywords: MHD; Free convective; Inclination; Poiseuille flow; Runge-Kutta method.; Climate Change; social crisis; collapse; Asymptomatic bacteriuria; pregnant woman; antibiotic resistance; risk factor